STUDENTS’ PERCEPTION OF SPADA UWGM AS LEARNING MANAGEMENT SYSTEM (LMS) IN WIDYA GAMA MAHAKAM SAMARINDA UNIVERSITY - Godefridus Bali Geroda (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Lecturers and students must be prepared to have technical knowledge and skills about easy applications and features that can accommodate online learning needs. It has been notified based on the researcher in pre research with the students. During the learning activities, the students find particular problems in learning online through SPADA as the LMS. However, they should know the system characteristic and functions to use the system effectively. Therefore, based on the background above, the researcher examined EFL students’ perceptions of the SPADA as a learning management system. The objectives of this research study are to find out what are students’ perception of SPADA UWGM as Learning Management System (LMS) in Widya Gama Mahakam Samarinda University. This study used qualitative research with case study approaches. The result showed that perception of using SPADA as the learning management system in the fifth semester of Class a English Education Department in Widya Gama Mahakam Samarinda University divided into three indicators of perception that are acceptance, understanding, and evaluation. Furthermore, from the student’s perception of acceptance the students stated that online learning can be said to be an effective learning resource when supported by adequate infrastructure such as good networks and the SPADA as the Learning Management System but the students still have difficulties in acceptance the material with SPADA as the Learning Management System